FORM AND PROCESS OF WORD ABBREVIATION IN ONLINE TRANSPORTATION SERVICE ADVERTISEMENTS ON THE @GRABISTIMEWA ACCOUNT - Aditya Putri, Aurelia; Mursia Ekawati, Mursia; Jendriadi Jendriadi, Jendriadi (Universitas Muhammadiyah Makassar, 2026)
The rapid development of technology has caused service provider companies to change strategies in advertising techniques, which also affects language change with the emergence of abbreviations. Abbreviation is the process of decapitating one lexeme or a combination of several lexemes, then turning into a new form. The purpose of this study is to analyze the use of abbreviations and the process of abbreviation formation in the online transportation service @grabistimewa account. This research uses descriptive qualitative method. It is analyzed using the agih method with the basic technique of BUL (Bagi Elemen Langsung), to divide the data so that it can be analyzed in depth related to its form and formation process. This research focuses on online transportation service advertisements on the @grabistimewa account from January to September 2025 with data in the form of words that contain abbreviations in advertising pamphlets. The results of this study show that there are 231 abbreviation data consisting of five forms of abbreviations, among others, 112 abbreviation data, 22 acronym data, 15 contraction data, 10 fragment data, and 72 letter symbol data. Meanwhile, in the formation process, the first letter of the abbreviation, the first three letters of the abbreviation, the first two letters of the abbreviation, the last three letters of the abbreviation, the first letter of the compound component, and the irregular abbreviation are found. Therefore, abbreviations in advertisements on social media are not only used to attract readers' attention, but become a strategy to simplify words in order to understand information more quickly.